2007
DOI: 10.1519/r-18385.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Short-Term Use of Testosterone Enanthate on Muscular Strength and Power in Healthy Young Men

Abstract: Use of testosterone enanthate has been shown to significantly increase strength within 6-12 weeks of administration (2, 9), however, it is unclear if the ergogenic benefits are evident in less than 6 weeks. Testosterone enanthate is classified as a prohibited substance by the World Anti-Doping Agency (WADA) and its use may be detected by way of the urinary testosterone/epitestosterone (T/E) ratio (16). The two objectives of this study were to establish (a) if injection of 3.5 mg.kg(-1) testosterone enanthate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Some studies have shown gains in body weight, girth, fat-free mass or lean body mass, but not in muscle strength [27][29], whereas others have shown gains in both muscle mass/girth and muscle strength [5], [8], [17], [30], [31], or in neither muscle mass/girth nor muscle strength after short term (from 17 days to 16 weeks) [32][35] or long term (2 years) [36] AAS administration. The present study showed that athletes with long term AAS supplementation had significantly higher leg lean mass compared to Clean athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown gains in body weight, girth, fat-free mass or lean body mass, but not in muscle strength [27][29], whereas others have shown gains in both muscle mass/girth and muscle strength [5], [8], [17], [30], [31], or in neither muscle mass/girth nor muscle strength after short term (from 17 days to 16 weeks) [32][35] or long term (2 years) [36] AAS administration. The present study showed that athletes with long term AAS supplementation had significantly higher leg lean mass compared to Clean athletes.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that supraphysiological doses of testosterone enhance maximal voluntary strength by increasing muscle mass and not by changing contractile properties, and the improvement in strength was dose-dependent [55]. Rogerson et al [56] observed an increase in output of work and power during cycle sprinting in subjects integrated with testosterone. The data suggest that testosterone may increase sprinting performance in humans as in animals [57].…”
Section: Cellular Mechanisms Responsible For the Effect Of Testostmentioning
confidence: 99%
“…The obtained results can be ascribed to the influence of testosterone and muscle mass. Previous studies have shown that there is a connection between the level of testosterone and the manifestation of muscle power [27,28]. We can assume that men at various levels of training advancement included in this research manifested approximately similar results of isokinetic power precisely because of having a higher level of testosterone and more muscle mass than women.…”
Section: Discussionmentioning
confidence: 60%